Effects of Acupuncture Applied to Sanyinjiao with Different Stimuli on Uterine Contraction and Microcirculation in Rats with Dysmenorrhea of Cold Coagulation Syndrome. (24th March 2014) - Hsu, Wing-sze; Shen, Xiao-yu; Yang, Jia-min; Luo, Li; Zhang, Ling; Qi, Dan-dan; Shen, Song-xi; Zhu, Shi-peng; Zhao, Ya-fang; Ren, Xiao-xuan; Guo, Meng-wei; Li, Xiao-hong; et al.
Abstract : In this study, we try to evaluate the effects of acupuncture stimulation with different amounts at Sanyinjiao (SP6) on uterine contraction and uterus microcirculation in rats with dysmenorrhea of cold coagulation syndrome and to explore whether there is direct relativity between "De qi" and needle stimulus intensity. Diestrus female rats were randomly divided into 4 groups, including saline control group, model control group, "A" stimulus group (with strong stimulus), and "B" stimulus group (with weak stimulus). We found that dysmenorrhea rats of the cold coagulation syndrome present a high intensity in uterine tension and high contraction of microvascular diameter. Acupuncture applied with two different stimuli could relieve the symptoms, but, compared with "B" stimulus, "A" stimulus leads to better outcomes on reducing uterine contraction and increasing diameter of uterine microvascular; moreover, hand manipulation during needling mediates the curative effect on the microvascular diameter. Our finding indicates that using thick needles and deep insertion with hand manipulation are more effective and achieve desired level of "De qi" in dysmenorrhea rats.